ANALISIS KANDUNGAN GIZI DONAT UBI UNGU (IPOMOEA BATATAS L.) SEBAGAI MAKANAN JAJANAN BERBASIS PANGAN LOKAL BAGI ANAK SEKOLAH - Riva Mustika Anugrah (Jurnal Gizi, 2020)
Doughnut as one of  popular snack by  school children.  Doughnut development is needed to improve nutritional quality  and physical characteristics. Purple sweet potato as a source of local food can be processed for addition ingredients of doughnut. The purpose of this research was to determine contained of nutrient and acceptance of purple sweet potato doughnut as snack based on local food for school children. This experiment investigated formulation of purple sweet potato doughnut  with the ratio of purple sweet potato: wheat flour  20:80 ( F1), purple sweet potato:wheat flour 30:70 (F2). Analyzed of protein nutrients with micro kjehdal, fat with soxhlet and carbohydrates with anthron. Statistical analysis of acceptance  used  Mann-Whitney test. The result in this study was analyzed of the  nutritional value of F1 sweet purple potato doughnut every serving (40g) containing energy: 158.46 kcal, Protein: 5 g, Fat: 9.92 g, Carbohydrates: 12.34 g and F2 energy: 169.51 kcal , Protein: 7.5 g, Fat: 11.32 g, Carbohydrates: 9.4 g. The acceptance test was performed  no differences in color, texture, taste and aroma in the two purple sweet potato donuts formulas (p≥0.05). The energy content of  F2 can contributed 10.27%  energy need of school children.